Social work and follow up to graduates at the Universidad Tecnica de Manabi - Barreiro, Leila Alava; Menendez, Fabian Gustavo Menendez; Medranda, Eva Alcivar; Sornoza, Karol Liceth Pico (International research journal of management, IT and social sciences, 2017)
The article presents an analysis of social work in the areas of health, education and social protection, exposing the role that should characterize social work professionals in the areas analyzed. It is characterized by the analysis of data related to the province of Manabí and especially to the city of Portoviejo. Some results related to the follow-up activities for graduates at the Universidad Tecnica de Manabí are presented, based on documentation investigated by the Monitoring Committee for Graduates and Labor Insertion of the career of Social Work of the university, in relation to the jobs That occupy the professionals and their intervention in the labor field. A survey was applied to 161 social workers who were graduated in the period 1984-2017, the results obtained demonstrate the significant aspects that allowed the graduates to insert themselves in the work to be done finding as more significant aspects to have the title of the career, personality And pre-professional experience.